Ethical dimensions of healthcare nudges: a PRISMA-ScR–guided scoping review and framework for responsible behavioral governance - Shang, Huijing; Xiong, Lingfang; Chen, Kefan; Tian, Renqiong; Tu, Jing; Shang, Xianhui (Frontiers in Public Health, 2025)
BackgroundNudging has gained momentum in healthcare as a behavioral strategy to support beneficial health choices. However, its ethical legitimacy remains contested, especially regarding autonomy, transparency, fairness, and risks of covert influence.ObjectiveThis scoping review synthesizes ethical debates on healthcare nudges and proposes governance principles to guide ethically responsible implementation.MethodsWe conducted a scoping review following the PRISMA-ScR framework across international and Chinese databases. Conceptual and empirical bioethics literature from 2013 to 2023 was analyzed through thematic synthesis.ResultsTwenty-three studies met inclusion criteria. Ethical concerns centered on autonomy (22/23), informed consent and transparency (4/23), equity and distributive fairness (2/23), and risk of unintended harm (1/23). Reflective nudges that support deliberation were more widely endorsed than covert defaults. Recent scholarship emphasizes transparency, proportionality, stakeholder participation, and equity audits as conditions for ethical legitimacy.ContributionTo our knowledge, this is the first review to systematically synthesize ethical dimensions of healthcare nudges using the PRISMA-ScR framework and to propose an actionable governance model for responsible behavioral regulation. The review advances ethical theory by integrating principlism, consequentialism, and deontology with cross-cultural public health ethics, and policy insights by identifying operational safeguards for health systems.ConclusionHealthcare nudges can be ethically justified when designed with transparency, meaningful opt-out options, proportionality of influence, and equity safeguards. Responsible behavioral governance requires culturally sensitive implementation, independent oversight, and continuous monitoring of autonomy and fairness outcomes. Future empirical work should examine real-world impacts on patient agency and equity across diverse clinical and cultural contexts.